Carbon dynamics of acid saline pokkali soil under long term fertiliser application in rice - Sharon Mathew (Academy of Climate Change Education and Research, 2016)
The amount of carbon in the atmosphere has increased by 30 per cent. The rising temperatures and carbon dioxide concentration and uncertainty in rainfall associated with climate change may have direct relationship with increased levels of carbon dioxide. One proposed method to reduce atmospheric carbon dioxide is to increase the global storage of carbon in soils with an added benefit in simultaneous enhancement in agricultural production. Soil organic carbon (SOC) is one of the main carbon reservoirs in the terrestrial ecosystem. It is important to study SOC dynamics and effects of organic carbon amendments in paddy fields and saline soils because of their vast expansion Objectives of the study were to estimate the soil organic carbon (C) status in acid saline soil and to assess the influence of long term fertilizer applications on soil carbon dynamics. Samples were collected from the experimental plot laid out in randomized block design with 10 treatments, each replicated four times with pokkali rice variety Vytilla 4 at RRS Vytilla, Kerala. The study revealed the baseline soil characteristics especially the soil carbon and its counterparts. Vertical distribution of SOC showed the storage profile of carbon and in cultivated sites a topsoil carbon sink (mostly labile carbon) is identified owing to increased fertiliser inputs whereas a potential subsoil sink (non labile carbon) is identified vertically downwards. However, the high content of non labile carbon in the subsurface showed the ability of Pokkali soil for carbon sequestrations. The labile carbon present in the surface soil resulted in the availability of nutrients to the plants which was evident from the high nutrient status of the control plot .all carbon fractions in the present study indicates the ability of Pokkali soils to sequester carbon. Therefore, the Pokkali ecosystem has to be maintained as such to mitigate the ill effects of global warming in the present climate change scenario.